How guilt drives emotional exhaustion in work–pet family conflict - Junça Silva, A. (Animals, 2024)
Work–pet family conflict has emerged as a novel form of work–life conflict, reflecting the increasingly significant role that pets play in modern families. Guided by role theory, work–pet family conflict is anticipated to produce outcomes similar to those of traditional work–life conflict. Accordingly, we developed a conceptual model to examine how work–pet family conflict affects employees’ emotional exhaustion. Drawing on role theory, we tested whether the experience of guilt serves as an affective mechanism linking work–pet family conflict to emotional exhaustion. Data were collected from 356 pet owners to empirically test the model. The results revealed a significant relationship between work–pet family conflict and emotional exhaustion, mediated by employees’ experienced guilt. This study underscores the relevance of work–pet family conflict as a distinct form of work–life conflict and highlights the role of guilt as a key emotional driver that contributes to employees’ emotional exhaustion in this context. Hence, organizations can delineate strategies to mitigate work–pet family conflict by offering flexible work arrangements, implementing pet-friendly policies, providing pet care benefits, and fostering a culture that supports work–life balance. These measures can potentially help employees better manage the demands of both work and pet responsibilities.